Decision support systems VI -- addressing sustainability and societal challenges : 2nd International Conference, ICDSST 2016, Plymouth, UK, May 23-25, 2016, Proceedings /: 2nd International Conference, ICDSST 2016, Plymouth, UK, May 23-25, 2016, Proceedings. (2016) - Unknown
No abstract available